Corpus-Based Study of Lexical Bundles in the Abstracts of High-Impact Research ‎Articles across Disciplines - Umi Khoirunnisa; Eri Kurniawan (JEELS (Journal of English Education and Linguistics Studies), 2025)
Lexical bundles are essential for creating coherent academic writing and for forming high-quality research articles. Researchers have previously examined lexical bundles in a number of academic fields and sections. However, there is a lack of investigation on cross-disciplinary comparisons in research article abstracts. Thus, this study seeks to examine the utilization of lexical bundles (LBs) in abstracts across disciplines. The analysis used a corpus-based study design to investigate the frequency, structural patterns, and function distributions of lexical bundles in abstracts across disciplines categorized as soft sciences (Linguistics, ELT, Psychology) and hard sciences (Electronic Engineering, Medicine, Biochemistry). To guarantee the representativeness of high-impact research articles, 180 abstracts of research articles, 30 from each discipline were chosen from high-citation Scopus-indexed journals. A descriptive quantitative approach was employed within Biber's (2004) structural taxonomy and Hyland's (2008b) functional classification, along with other categories to provide comprehensive understanding of LBs manifestations. The results indicate significant disciplinary commonalities in LB usage albeit numerous noticeable variations. A bias for phrasal over clausal constructs was observed in the structural use of bundles in both the Hard and Soft Sciences, with noun phrase-based bundles being the most prevalent. In terms of functionality, research-oriented bundles predominated in both domains, with Soft Sciences preferring description bundles and Hard Sciences stressing topic bundles. This study sheds light on disciplinary conventions in abstract writing and emphasizes the significance of understanding the structural and functional differences in LBs in cross-disciplinary engagement and effective academic communication.